2010
DOI: 10.1007/s11663-010-9439-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Holding Liquid Aluminum Alloys on Oxide Film Content

Abstract: Melts of commercially pure liquid aluminum, and an Al-7Si-0.3Mg alloy, were cast into molds designed to produce entrainment of oxide film defects. The melts were held for periods of up to 20 minutes to investigate whether changes in the oxide film defects in the melt could occur, once sufficient time had elapsed for consumption of their internal atmosphere. The alloys were characterized by the determination of their Weibull modulus, examination of fracture surfaces under scanning electron microscopy (SEM), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…Uludag et al [26][27][28][29] studied the influence of Sr on bifilm index. It was found that addition of Sr had decreased the size and length of pores which was attributed to the healing of bifilms as was reported by Ramin [25,30,31].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Uludag et al [26][27][28][29] studied the influence of Sr on bifilm index. It was found that addition of Sr had decreased the size and length of pores which was attributed to the healing of bifilms as was reported by Ramin [25,30,31].…”
Section: Introductionsupporting
confidence: 59%
“…It was also reported that Sr had decreased porosity. Ramin and Griffiths [25] reported that in the presence of Sr, two folded oxide skins bind together, which was described by Campbell [1] as the healing mechanism. Thereby the porosity was decreased since bifilms were unable to unravel.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible explanation for the formation of the hollow area is the flotation of real double oxide film defects that were present in the lower bar, which expanded due to the diffusion of hydrogen into their atmospheres, [16][17][18] to be accumulated underneath the oxide layer at the top of the lower bar (named 'oxide layer 1' in Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…1). The rate of flotation of oxide layers is known [16][17][18] to depend on the hydrogen content of the melt, which in turn depends on the rate of reaction of the melt with ambient moisture. As the Mg content of the melt increased, this reaction rate increased; 19 therefore, the hydrogen content of the melt and the rate of the flotation of the oxide films, and hence the possibility of the formation of the hollow area underneath the oxide layer, increased.…”
Section: Discussionmentioning
confidence: 99%
“…These spinel particles are probably newly formed and do not settle to the bottom of the furnace during the holding process. Based on the results and observations above, Stokes's law can be used to predict the settling velocity of oxide particles with different sizes in the furnace during holding treatment [17]. The settling velocity of an inclusion particle can be expressed as the following equation.…”
Section: Effect Of Holding Time On the Inclusionsmentioning
confidence: 99%